Treating Familial Identity Theft Using the Collaborative Relational Model - Axton E Betz-Hamilton; Meghaan Lurtz; Nathan Astle (Journal of Financial Therapy, 2024)
Nearly one-third of all identity theft victims have their identity stolen by a family member. This type of identity theft is known as familial identity theft. Familial identity theft can lead to a host of negative financial, emotional, and physical consequences for the victim. While various governmental and private resources are available to help victims recover, they are siloed and fragmented, leaving victims to navigate how to identify their needs and find appropriate resources on their own. This paper describes the potential efficacy of the collaborative relational model in helping victims recover financially and emotionally by utilizing a fictionalized client case vignette to apply the model.
Keywords: collaborative relational model; familial identity theft; trauma